The Influence of Work Ability, Coordination and Work Environment on The Performance of Employees at The Regional Personnel Agency in South Kalimantan Province (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2023)
ABSTRACTThis study aims to determine both partially and simultaneously how much influence the work ability, coordination and work environment has on the employee performance of the South Kalimantan Provincial Civil Service Agency and the variables that have a dominant influence on the employee performance of the Regional Civil Service Agency of South Kalimantan Province. The method used in this study is a quantitative method and with a population of 91 (ninety one), samples were taken with the census sampling technique of 91 (ninety one) people, the research instruments were validity and reliability tests, the data were tested using regression multiplelinear. The results of this study indicate that (1) Work Ability, Coordination and Work Environment simultaneously have a significant effect on the Employee Performance of Regional Personnel Board of South Kalimantan Province; (2) Work Ability, Coordination and Work Environment partially significant influence on Employee Performance of Regional Personnel Board of Kalimantan Province South; and (3) The variable that has dominant influence on the Employee Performance of the Regional Personnel Board of South Kalimantan Province is coordination. R-Square is 0.309, which means that the variation in the contribution of all independent variables to the dependent variable is 30.9% while the remaining 69.1% is explained by other causes outside of this study. Keywords: Work Ability, Coordination, Work Environment and Performance.